Genetic and physiological variability of Meloidogyne incognita populations from cotton farms in western Bahia, and evaluation of resistance in Gossypium spp. genotypes - Lopes, Carina Mariani Leite (2019)
Tese (doutorado) — Universidade de Brasília, Instituto de Ciências Biológicas, Departamento de Fitopatologia, Programa de Pós-Graduação em Fitopatologia, 2019.